Educational Tourism as an Effective Learning Model at Vredeburg Fort Museum Yogyakarta Indonesia - Wijayanti, Ani (E-Journal of Tourism, 2018)
The Vredeburg Fort Museum became the main destination of educational tourism. Edu-tourism attractions offered by Vredeburg Fort Museum able to realize educational tourism experience and become a source of learning, not just a source of information. This research is a descriptive survey research. Data were obtained through a survey of 200 respondents selected by purposive sampling and analyzed using three box method. The survey results recorded Vredeburg Fort Museum offers a very varied tourist attraction, with a high index value, which is 150.71, while the learning experience of history science is 145.5. The results is Vredeburg Fort Museum applied cooperative learning concept through the implementation of several elements in the management of educational tourism, including; the team of planners, tourism content, events, local community involvement, tour operators, media, curriculum, teachers, educators, tour flow, and organization. The concept of learning is formed in two spaces, namely classroom and practical experience involving various stakeholders. The concept of learning is very effective to understand the historical messages offered by managers through collectibles, as well as bridges between educational institutions and Vredeburg Fort Museum to get practical training for learners. Keyword: edu-tourism, learning model, tourism experience, educator, museum